Extended Validation Study of the Thinking and Creative Style Scale: Development of a Shorter Version - Wechsler,Solange Muglia (2016)
ABSTRACT There are several measures of cognition and creative styles, however few of them are valid and short enough to be administered in different settings. Therefore, this study had two purposes: to reanalyze and obtain validity evidence of the Scale of Thinking and Creative Scale (STCS), developed by Wechsler, measuring five styles, based on a progression of increasingly rigorous exploratory and confirmatory factor analytic procedures, and (b) to provide a viable psychometrically sound short version of this scale. Based on a sample of 1,752 Brazilians (55% women; ages 14 to 70) living in four states (93% from Sao Paulo), results strongly supported five dimensions of thinking and creative style, thus indicating the validity and reliability of the abridged STCS version.